Constructing ultrathin film with "memory" photocatalytic activity from monolayered tungstate nanodots. Issue 43 (5th April 2016) - Xing, Zheng; Zeng, Xiangkang; Deletic, Ana; McCarthy, David; Wang, Gen; Zhang, Xiwang
Abstract : This work describes an ultrathin transparent film of monolayered tungstate nanodots, which can perform post-irradiation catalytic antibacterial reactions. Abstract : An ultrathin film of monolayered tungstate nanodots was successfully fabricated via a layer-by-layer self-assembly method, which shows a "memory" photocatalytic activity. Photoinduced electrons are quickly stored in the ultrathin film upon irradiation due to the reduction of W 6+ to W 5+, and discharged to produce superoxides, enabling post-irradiation antibacterial activities.